Az esm' . Az esm' . I Am . Азъ есмь - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. A program about the fate of Soviet nonconformist artists. Featured in the program: Shemiakin, Mikhail Mikhailovich (Painter); Drapkina, Alla (Writer) Передача о судьбе советских художников-нонконформистов. В программе участвуют: Шемякин, Михаил Михайлович (Художник); Драпкина, Алла (Писательница)